1985
DOI: 10.1037/0022-3514.49.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time limits and task types on task performance and interaction of four-person groups.

Abstract: This study examined the effects of time limits and task types on the quality and quantity of group performance and patterns of group interaction. The results were interpreted in terms of social entrainment, a concept that refers to the altering of social “rhythms” or patterns by external conditions (such as time limits), and to the persistence of such new rhythms over time. Groups performed two tasks of a single task type for two trials of different durations (10 min followed by 20 min, or 20 min followed by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(152 citation statements)
references
References 15 publications
7
142
1
2
Order By: Relevance
“…We found three empirical studies that demonstrated a negative effect of time pressure on creativity. Kelly and McGrath (1985) conducted an experimental study and found that groups facing time pressure generated less creative ideas than groups with more time to perform their work. Andrews and Smith (1996) also found that the more time pressure marketing professionals perceived, the less creative they were when developing creative ideas.…”
Section: Perceived Time Pressure and Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…We found three empirical studies that demonstrated a negative effect of time pressure on creativity. Kelly and McGrath (1985) conducted an experimental study and found that groups facing time pressure generated less creative ideas than groups with more time to perform their work. Andrews and Smith (1996) also found that the more time pressure marketing professionals perceived, the less creative they were when developing creative ideas.…”
Section: Perceived Time Pressure and Creativitymentioning
confidence: 99%
“…Nevertheless, the results of previous studies were inconclusive and inconsistent (Amabile et al 2002;Baer & Oldham 2006). Some demonstrated a negative effect of time pressure on creativity (Kelly & McGrath 1985), others found no effect (Amabile & Gryskiewicz 1989), and some even found a positive effect (e.g. Andrews & Farris 1972;Ohly & Fritz 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dansky & Silverman, 1973;Dentler & Mackler, 1964;Drwal, 1973;Sandlund, Linnarud, & Norlander, 2001;Ward, Kogan, & Pankove, 1972), untimed (e.g. Cropley, 1972;Johns & Morse, 1997;Kelly & McGrath, 1985;Torrance, 1969) or both conditions (e.g. Adams, 1968;Vernon, 1971), while other studies reported contrary results (e.g.…”
Section: Testing Conditionsmentioning
confidence: 49%
“…La falta de un mínimo nivel de análisis en el que apoyar la solución adaptada puede provocar un cierta desconfianza en la solución adoptada e impedir su posterior aplicación para la resolución de otros problemas similares. Si bien es cierto que un determinado nivel de presión de tiempo puede acelerar el ritmo de resolución, ciertas investigaciones sugieren que esto es un factor motivador sólo hasta un determinado punto (KELLY y MCGRATH, 1985).…”
Section: Aprendizaje Situacionalunclassified